Fuzzy dematel method to evaluate the dimensions of marketing resources: An application in SMEs - Altuntas, Serkan; Yilmaz, Mustafa Kemal (Journal of Business Economics and Management, 2016)
Identifying the cause and effect factors of marketing resources and prioritizing them with respect to their level of importance can build superior market performance for companies. Although there have been some studies in the literature which have used marketing resource dimensions to conduct their research, these studies have not considered the relationships between marketing resource dimensions. Therefore, the aim of this study is to identify the cause and effect factors of marketing resources and to prioritize them in terms of their importance using the fuzzy Decision-Making Trial and Evaluation Laboratory method. The findings of this study suggest that the dimension managerial capabilities, composed of financial management, effective human resource managementand good operations management expertise, exerts a greater influence on marketing strategy than other criteria. In addition, the criterion credibility with customers through being well established in the market is the most important aspect of marketing resources.